The soluble receptor for advanced glycation end products is potentially predictive of pulmonary arterial hypertension in systemic sclerosis - Atzeni, Isabella M.; Al-Adwi, Yehya; Doornbos-van der Meer, Berber; Roozendaal, Caroline; Stel, Alja; van Goor, Harry; Gan, C. Tji; Dickinson, Michael; Timens, Wim; Smit, Andries J.; Westra, Johanna; Mulder, Douwe J. (Frontiers in Immunology, 2023)
Introduction: Pulmonary arterial hypertension (PAH) and interstitial lung disease (ILD) are the leading causes of death in systemic sclerosis (SSc). Until now, no prospective biomarker to predict new onset of SSc-ILD or SSc-PAH in patients with SSc has reached clinical application. In homeostasis, the receptor for advanced glycation end products (RAGE) is expressed in lung tissue and involved in cell-matrix adhesion, proliferation and migration of alveolar epithelial cells, and remodeling of the pulmonary vasculature. Several studies have shown that sRAGE levels in serum and pulmonary tissue vary according to the type of lung-related complication. Therefore, we investigated levels of soluble RAGE (sRAGE) and its ligand high mobility group box 1 (HMGB1) in SSc and their abilities to predict SSc-related pulmonary complications. Methods: One hundred eighty-eight SSc patients were followed retrospectively for the development of ILD, PAH, and mortality for 8 years. Levels of sRAGE and HMGB1 were measured in serum by ELISA. Kaplan-Meier survival curves were performed to predict lung events and mortality and event rates were compared with a log-rank test. Multiple linear regression analysis was performed to examine the association between sRAGE and important clinical determinants. Results: At baseline, levels of sRAGE were significantly higher in SSc-PAH-patients (median 4099.0 pg/ml [936.3-6365.3], p = 0.011) and lower in SSc-ILD-patients (735.0 pg/ml [IQR 525.5-1988.5], p = 0.001) compared to SSc patients without pulmonary involvement (1444.5 pg/ml [966.8-2276.0]). Levels of HMGB1 were not different between groups. After adjusting for age, gender, ILD, chronic obstructive pulmonary disease, anti-centromere antibodies, the presence of puffy fingers or sclerodactyly, use of immunosuppression, antifibrotic therapy, or glucocorticoids, and use of vasodilators, higher sRAGE levels remained independently associated with PAH. After a median follow-up of 50 months (25-81) of patients without pulmonary involvement, baseline sRAGE levels in the highest quartile were predictive of development of PAH (log-rank p = 0.01) and of PAH-related mortality (p = 0.001). Conclusions: High systemic sRAGE might be used as a prospective biomarker for patients with SSc at high risk to develop new onset of PAH. Moreover, high sRAGE levels could predict lower survival rates due to PAH in patients with SSc.